Quién fue Costa / Pedro Martínez Baselga ; introducción: Eloy Fernández Clemente - Fernández Clemente, Eloy (1942-); Martínez Baselga, Pedro (1862-1925)
Reprod. facs. de la ed. de: Zaragoza : Tip. G. Casaąl